Deities, archers, and planners in the era of decentralization / (Acc: 2543) - Karma Ura, 1961- (Bhutan : Karma Ura, 2004)
Collection of writings predominantly on socio-cultural life and decentralization in government of Bhutan.
Keywords: Decentralization in government